Totalitarianism and the questionable legitimation of conflict through propaganda in Marjane Satrapi’s Persepolis and Art Spiegelman’s Maus - Fălăuș, Anamaria (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2024)
Marjane Satrapi’s graphic novel Persepolis is far from being a simple coming-of-age narrative. The autobiographical tale, projected onto the background of a relatively hostile country, tells the story of a young girl growing up in revolutionary Iran, a place where threats of violence, arrest, and torture are everyday fears. Art Spiegelman’s graphic novel Maus is the story of the Holocaust seen through the eyes of the main character, Vladek, which juxtaposes the minutiae of day-to-day life with the enormity of the experience. This paper analyzes the social, historical, and cultural context that led to the Iranian Revolution and the Iraq-Iran war, on the one hand, and to the greatest extermination of the Jews in history, on the other. It aims to prove how lies, misconception, and murderous actions can be justified by virtues or allegedly good intentions.